2020
DOI: 10.1111/jsr.13030
|View full text |Cite
|
Sign up to set email alerts
|

Acute sleep deprivation elevates brain and body temperature in rats

Abstract: Brain temperature is a sensitive indicator of brain health. It largely depends upon the metabolic activity of brain cells, cerebral blood flow and blood temperature (Hayward & Baker, 1969). It is regulated within narrow limits in mammals (Satinoff, 1978; Schmidt-Nielsen 1989). Minor changes in brain temperature result in significant changes in neuronal metabolism and firing frequency. This increased temperature worsens the clinical conditions by changing the neuronal membrane properties and spike activity (Kiy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…Similar to the present study, an increase in Tb across 24‐h SD using gentle handling followed by a decline during recovery was reported in rats (Vishwakarma et al., 2020). In the present study, both extended wakefulness and associated motor activity are likely to have contributed to the Tb increase during acute SD.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to the present study, an increase in Tb across 24‐h SD using gentle handling followed by a decline during recovery was reported in rats (Vishwakarma et al., 2020). In the present study, both extended wakefulness and associated motor activity are likely to have contributed to the Tb increase during acute SD.…”
Section: Discussionsupporting
confidence: 91%
“…Sleep is closely linked to other physiological processes, such as body temperature (Tb) regulation (Harding, Franks, & Wisden, 2020; Szymusiak, 2018). In addition, Tb is impacted by CSR (Caron & Stephenson, 2010; Everson & Szabo, 2009) and acute sleep deprivation (Dispersyn et al., 2017; Vishwakarma, Sharma, Singh, Jaryal, & Mallick, 2020), but whether the Tb response to acute sleep loss is affected by CSR exposure remains to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the thermoregulatory responses, RSD rats presented greater T CORE at exercise initiation, a finding that agrees with other studies, in which short-term REM/total sleep deprivation increased the T CORE of the animals [23][24][25]. Jaiswal et al [24] observed marked hyperthermia (~1.2°C rise) already on the 1st day of RSD; this hyperthermia was then gradually reversed with rats presenting normal T CORE levels within 6-8 days of RSD.…”
Section: Discussionsupporting
confidence: 89%
“…In this sense, REM sleep deprivation (RSD) adversely affects several body functions, including food intake, energy metabolism, body weight [19], and the regulation of T CORE . Several authors demonstrated that total sleep deprivation and RSD modify the thermoregulatory responses in rats, with either report of hypothermia [20][21][22][23][24] or hyperthermia [20,21,[23][24][25]. Of note, the predominant thermoregulatory manifestation depends on the duration of sleep deprivation: the initial hyperthermia is usually replaced by hypothermia as deprivation progresses and the risk of dying increases [20,21,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Elevation in the intracranial pressure (ICP) may reduce intracranial compliance (ICC), what is the equilibrium among intracranial content (brain, blood volume and cerebrospinal fluid), 4 impacting cerebral perfusion and cellular metabolism 5 . Several mechanisms linking obesity with chronic ICH have been proposed, mainly as disturbances of cerebrospinal fluid circulation, 6,7 dysregulation of the metabolic neuroendocrine axis, 8 compression of thoracic and abdominal organs impairing cerebral venous return, 9 sleep apnea leading to cerebral hemodynamics disorders (CHD) 6,10,11 and brain temperature elevation 12 . Additionally to genetic and epigenetic determinants, 13 these factors may also play a role in increasing risks of neurodegenerative diseases (NDD) development in this population.…”
Section: Introductionmentioning
confidence: 99%